Morphology and DNA barcoding reveal a new species of Eudicella from East Africa (Coleoptera: Scarabaeidae: Cetoniinae) - Seidel, Matthias (Zootaxa, 2016)
A new species of Eudicella White, 1839 (Coleoptera: Scarabaeidae: Cetoniinae), is described from Uganda and Kenya: E. nana new species. Morphological and genetic analyses of the new taxon and phenotypically allied species are given. Eudicella nana is compared with its hypothesized sister species, E. darwiniana Kraatz, 1880, and diagnostic characters that distinguish it from other species occurring in the same region are provided.